Assessing the extent and effectiveness of diabetes self-management education in public health care institutions in Harare, Zimbabwe - Nkomani, Sanele (Stellenbosch : Stellenbosch University, 2016)
Thesis (MNutr)--Stellenbosch University, 2016.